Mucosal immunization with a flagellin-adjuvanted Hgp44 vaccine enhances protective immune responses in a murine Porphyromonas gingivalis infection model. Issue 12 (2nd December 2017) - Puth, Sao; Hong, Seol Hee; Park, Mi Jin; Lee, Hye Hwa; Lee, Youn Suhk; Jeong, Kwangjoon; Kang, In-Chol; Koh, Jeong Tae; Moon, Byounggon; Park, Sang Chul; Rhee, Joon Haeng; Lee, Shee Eun
ABSTRACT: Chronic periodontitis is caused by interactions between the oral polymicrobial community and host factors. Periodontal diseases are associated with dysbiotic shift in oral microbiota. Vaccination against periodontopathic bacteria could be a fundamental therapeutic to modulate polymicrobial biofilms. Because oral cavity is the site of periodontopathic bacterial colonization, mucosal vaccines should provide better protection than vaccines administered systemically. We previously reported that bacterial flagellin is an excellent mucosal adjuvant. In this study, we investigated whether mucosal immunization with a flagellin-adjuvanted polypeptide vaccine induces protective immune responses using a Porphyromonas gingivalis infection model. We used the Hgp44 domain polypeptide of Arg-gingipain A (RgpA) as a mucosal antigen. Intranasal (IN) immunization induced a significantly higher Hgp44-specific IgG titer in the serum of mice than sublingual (SL) administration. The co-administration of flagellin potentiated serum IgG responses for both the IN and SL vaccinations. On the other hand, the anti-Hgp44-specific IgA titer in the saliva was comparable between IN and SL vaccinations, suggesting SL administration as more compliant vaccination route for periodontal vaccines. The co-administration of flagellin significantly potentiated the secretory IgA response in saliva also. Furthermore, mice administered a mixture of Hgp44 and flagellin via the IN and SL routes exhibited significant reductions in alveolar bone loss induced by live P. gingivalis infections. An intranasally administered Hgp44-flagellin fusion protein induced a comparable level of Hgp44-specific antibody responses to the mixture of Hgp44 and flagellin. Overall, a flagellin-adjuvanted Hgp44 antigen would serve an important component for a multivalent mucosal vaccine against polymicrobial periodontitis.